Kebijakan Hukum Pidana terhadap Revenge Porn di Indonesia - Rini Novita (Universitas Medan Area, 2026)
The development of information and communication technology has led to the emergence of various forms of cybercrime, one of which is revenge porn, namely the distribution of intimate content without the victim's consent with the intention of humiliating, threatening, or seeking revenge. This offense causes serious psychological, social, and economic impacts and constitutes a violation of the right to privacy and human dignity. This study aims to analyze criminal law policies regarding revenge porn in Indonesia and evaluate the effectiveness of existing legal regulations in protecting victims. This research employs a normative legal research method using statutory and conceptual approaches. Data were collected through library research consisting of primary, secondary, and tertiary legal materials and analyzed qualitatively using a descriptive-analytical method. The results indicate that the handling of revenge porn initially relied on the provisions of the Indonesian Criminal Code and the Electronic Information and Transactions Law, which have not provided optimal legal protection for victims. The enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes represents a progressive step, as it provides a clearer legal basis for addressing electronic-based sexual violence. Nevertheless, its implementation still faces challenges, including limitations in digital evidence, insufficient understanding among law enforcement officers, and victims' reluctance to report incidents due to social stigma. Therefore, strengthening criminal law policies through repressive, preventive, and rehabilitative measures is necessary to improve victim protection and enhance the effectiveness of combating revenge porn in Indonesia.